Eksplorasi Etnomatematika Pada Permainan Tradisional Dedo Gomo dan Gomo Telu di Wolowuwu, Kab. Ende, NTT Serta Integrasinya dalam Pembelajaran Matematika - Magdalena Wangge (Haumeni Journal of Education, 2023)
Traditional games are one of the cultures that began to fade along with the development of science and technology. This also happens to the people in Wolowuwu, Wolowaru sub-district, Ende district, NTT, namely the dedo gomo and gomo telu games. The purpose of this research is to identify ethnomathematics and mathematical concepts in dedo gomo and gomo telu games and their integration in mathematics learning. This type of research is qualitative research with research stages ranging from pre-field, field work to data analysis. In the data analysis stage, data reduction, data display, and conclusion drawing are carried out. The results obtained are that in the dedo gomo and gomo telu games, ethnomathematics activities are found, namely counting, locating, measuring, designing, playing, and explaining. Then the mathematical concepts found include integer operations, geometry, length measurement, arithmetic series, number patterns, and opportunities. One form of integration in mathematics learning is to prepare learning tools based on traditional game culture with contextual learning models.